Synthesis of Heterocycles by Metathesis Reactions - Prunet, Joëlle; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
Synthesis of Heteroaromatic Compounds by Alkene and Enyne Metathesis -- The Synthesis of Cyclic Ether-Containing Natural and Non-natural Products by Metathesis Reactions -- Metathetic Synthesis of Common and Medium-Sized Lactones: The State of the Art -- Synthesis of Amine-Containing Heterocycles by Metathesis Reactions: Recent Advances and Opportunities -- Synthesis of Lactams by Metathesis Reactions -- Synthesis of Cyclic Peptides and Peptidomimetics by Metathesis Reactions -- Synthesis of Macrocycles other than Peptides by Metathesis -- Synthesis of P-, S-, Si-, B-, and Se-Heterocycles via Ring-Closing Metathesis.
Keywords: Chemistry, Organic; Chemistry, Technical; Inorganic chemistry; Organic Chemistry; Industrial Chemistry; Inorganic Chemistry